Curcumin-Loaded Platelet Membrane Bioinspired Chitosan-Modified Liposome for Effective Cancer Therapy - Shengli Wan; Qingze Fan; Yuesong Wu; Jingqing Zhang; Gan Qiao; Nan Jiang; Jie Yang; Yuanzhi Liu; Jingyan Li; Sawitree Chiampanichayakul; Singkome Tima; Fei Tong; et al. (MDPI AG, 2023)
Cancer is a serious threat to human health, and chemotherapy for cancer is limited by severe side effects. Curcumin (CUR) is a commonly used natural product for antitumor treatment without safety concerns. However, low bioavailability and poor tumor accumulation are great obstacles for its clinical application. Our previous research has demonstrated that platelet membrane-camouflaged nanoparticles can efficiently ameliorate the in vivo kinetic characteristics and enhance the tumor affinity of payloads. Nevertheless, the antitumor efficiency of this formulation still needs to be thoroughly investigated, and its drug release behavior is limited. Herein, CUR-loaded platelet membrane bioinspired chitosan-modified liposome (PCLP-CUR) was constructed to improve CUR release. PCLP-CUR was shown to have long retention time, improved bioavailability, strong tumor targeting capacity and effective cellular uptake. The incorporation of chitosan enabled PCLP-CUR to release cargoes quickly under mild acidic tumor conditions, leading to more complete drug release and favoring subsequent treatment. Both in vitro and in vivo investigations showed that PCLP-CUR could significantly enhance the anticancer efficacy of CUR with minimal side effects through biomimetic membrane and chitosan modification. In summary, this developed delivery system can provide a promising strategy for tumor-targeting therapy and phytochemical delivery.